Impact of doping and geometry on breakdown voltage of semi-vertical GaN-on-Si MOS capacitors. (November 2022) - Favero, D.; De Santi, C.; Mukherjee, K.; Borga, M.; Geens, K.; Chatterjee, U.; Bakeroot, B.; Decoutere, S.; Rampazzo, F.; Meneghesso, G.; Zanoni, E.; Meneghini, M.
Abstract: For the development of reliable vertical GaN transistors, a detailed analysis of the robustness of the gate stack is necessary, as a function of the process parameters and material properties. To this aim, we report a detailed analysis of breakdown performance of planar GaN-on-Si MOS capacitors. The analysis is carried out on capacitors processed on different GaN bulk doping (6E18 Si/cc, 6E17 Si/cc and 2.5E18 Mg/cc, p-type), different structures (planar, trench-like) and different geometries (area, perimeter and shape). We demonstrate that (i) capacitors on p-GaN have better breakdown performance; (ii) the presence of a trench structure significantly reduces breakdown capabilities; (iii) breakdown voltage is dependent on area, with a decreasing robustness for increasing dimensions; (iv) breakdown voltage is independent of shape (rectangular, circular). TCAD simulations, in agreement with the measurements, illustrate the electric field distribution near breakdown and clarify the results obtained experimentally. Highlights: Gate stack breakdown of vertical and semi-vertical trench GaN power devices Influence of type (p or n) and concentration of GaN doping on breakdown voltage MOS capacitors reliability dependence on gate geometry Impact of trench formation in the gate stack of GaN power devices